FACTORS AFFECTING PRICE EARNING RATIO OF COMPANY’S SHARE IN THE MANUFACTURE SECTOR - Purwaningrum, Endang (Politeknik Negeri Jakarta, 2011)
Abstract This research is aimed to know factors significantly affecting Price Earning Ratio of manufacturing companies listed in Indonesian Stock Exchange listed in Indonesia Stock Exchange in the period of 2005 up to 2007. Using Multiple Regression Model, this research resulting summarises condition as follows : (a). Dividend Payout Ratio significantly affects Price Earning Ratio. (b). Return On Equity significantly affect to Price earning ratio. (c). Operating Profit Margin significantly affect to Price Earning Ratio. (d). The independent variables such as Dividend Payout Ratio, Return On Equity and Operating Profit Margin significantly affect the dependent variable Price Earning Ratio. From the result of the research, it can be implicated that investors should consider divident payout ratio, return on equity, and operating profit margin before investing their capital to share, especially in manufacture companies. For the emitens, they also have to consider them in order to increse their price earning ratio. Key words: DPR, ROE, OPM, PER. Abstrak